The Uses of Refutation and the Postulation of Unhypothetical Principles in RepublicVI-VII and the Sophist - Álvarez, Lucas (Revista Archai, 2022)
Following the proposal of interpreters who deal with the continuity of Plato’s methodology throughout his work, this paper will consider the Sophist dialogue as a convergence point for the Socratic refutation and for the hypothetical method displayed in Republic. Specifically, we will try to identify in this dialogue the highest point of the said method, i.e. the non-hypothetical principle mentioned by Socrates. In addition, this task will lead us to consider, on one hand, the relationship between Plato and his master and, on the other, the place the Sophist and his main interlocutor, the Eleatic Stranger, deserve within the framework of Plato’s philosophical project.